Essential oil composition of leaves and inflorescences of Elsholtzia densa Benth. from western Himalaya. Issue 3 (4th May 2019) - Chauhan, Amit; Venkatesha, K. T.; Padalia, Rajendra C.; Singh, Ved. R.; Verma, Ram S.; Chanotiya, Chandan S.
ABSTRACT: The essential oil compositions of leaves and inflorescences of Elsholtzia densa Benth. from western Himalaya were studied and compared using gas chromatography-flame ionization detector and gas chromatography-mass spectrometry. Altogether, forty constituents comprising 83.3–83.7% of essential oil composition were identified. The leaf essential oil of E. densa was characterized by citral (52.2%), geranyl acetate (3.3%) and geraniol (3.1%), whereas the inflorescence essential oil of E. densa was found to be dominated by pinocarvone (51.9%), cis -pinocamphone (5.2%) and citronellyl acetate (3.4%). The essential oil compositions were compared with earlier reports on Elsholtzia spp. from different geographic regions that revealed noteworthy compositional variability.